2017
DOI: 10.1186/s12916-017-0821-9
|View full text |Cite
|
Sign up to set email alerts
|

Are potentially clinically meaningful benefits misinterpreted in cardiovascular randomized trials? A systematic examination of statistical significance, clinical significance, and authors’ conclusions

Abstract: BackgroundWhile journals and reporting guidelines recommend the presentation of confidence intervals, many authors adhere strictly to statistically significant testing. Our objective was to determine what proportions of not statistically significant (NSS) cardiovascular trials include potentially clinically meaningful effects in primary outcomes and if these are associated with authors’ conclusions.MethodsCardiovascular studies published in six high-impact journals between 1 January 2010 and 31 December 2014 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…While the measured actual difference of 0.05 at 12 weeks is lower than the MID of 0.07, it is noted that the MID lies within the 95% CI: (0.01–0.09). It has been shown that clinically meaningful results can be concluded based on the position of the MID within the CI 20,21 . To our knowledge, there are 2 other RCTs comparing robotic to VATS lung resection 22,23 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the measured actual difference of 0.05 at 12 weeks is lower than the MID of 0.07, it is noted that the MID lies within the 95% CI: (0.01–0.09). It has been shown that clinically meaningful results can be concluded based on the position of the MID within the CI 20,21 . To our knowledge, there are 2 other RCTs comparing robotic to VATS lung resection 22,23 …”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that clinically meaningful results can be concluded based on the position of the MID within the CI. 20,21 To our knowledge, there are 2 other RCTs comparing robotic to VATS lung resection. 22,23 The ROMAN study enrolled patients with T1-T2, N0-N1 NSCLC who were randomized to either RTS or VATS lung resection (lobectomy and segmentectomy).…”
Section: Discussionmentioning
confidence: 99%
“…There is no guideline providing any strict recommendation on how this interpretation can be achieved. In recent years it has been increasingly recommended by several authors [ 33 36 ] to also judge the clinical relevance of study findings. In our study, there is no disadvantage/harm for patients through the intervention and there is proven benefit in terms of patient satisfaction and costs.…”
Section: Discussionmentioning
confidence: 99%